2020
DOI: 10.1097/gox.0000000000003265
|View full text |Cite
|
Sign up to set email alerts
|

Meshed Acellular Dermal Matrix in Immediate Prepectoral Implant-based Breast Reconstruction

Abstract: Background: Prepectoral implant placement has many potential advantages in immediate breast reconstruction. Acellular dermal matrices (ADMs) are commonly used in these surgeries. ADM meshing may enhance integration, decrease seroma and infection rates, and reduce surgical costs. Methods: This was a retrospective, single-center study of 49 women (71 breasts) undergoing immediate, prepectoral, implant-based breast reconstruction with 2:1 meshed, bovine-derived ADM (SurgiMend)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
(13 reference statements)
0
5
1
1
Order By: Relevance
“…Studies currently available on PPBR and fenestrated ADMs seem to confirm this hypothesis. Compared with 2.1% CC incidences reported in the iBAG study ( 53 ) and the weighted mean of 2.06% in this study, which is calculated with the Braxon® continuous collagen sheet, fenestrated-ADM-assisted PPBRs outline higher CC incidences: out of 71 breasts, Scheflan et al found an incidence rate of 8.5% of CC ( 119 ), while in the same year, Fin et al recorded 6% ( 120 ). More recently, Wazir et al reported a 12.5% incidence rate ( 121 ).…”
Section: Discussioncontrasting
confidence: 59%
“…Studies currently available on PPBR and fenestrated ADMs seem to confirm this hypothesis. Compared with 2.1% CC incidences reported in the iBAG study ( 53 ) and the weighted mean of 2.06% in this study, which is calculated with the Braxon® continuous collagen sheet, fenestrated-ADM-assisted PPBRs outline higher CC incidences: out of 71 breasts, Scheflan et al found an incidence rate of 8.5% of CC ( 119 ), while in the same year, Fin et al recorded 6% ( 120 ). More recently, Wazir et al reported a 12.5% incidence rate ( 121 ).…”
Section: Discussioncontrasting
confidence: 59%
“…Four different reviewers performed title and abstract review. Full-text review was conducted for 355 articles; 33 studies were eligible and underwent data extraction 16,17,29–62 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“… 21 It is speculated that the protective layer provided by the ADM between the implant and native tissue helps to slow the inflammatory process and limits the pathogenesis. However, with the growing popularity of meshing the matrix for better expansion and lower costs, 22 this ADM-assisted advantage in breast reconstruction may no longer exist. Currently, only one study by Maisel Lotan et al assessed fenestrated versus meshed ADM and found no differences in capsular contracture rates (2.7 vs. 5.2%; p = 0.342).…”
Section: Discussionmentioning
confidence: 99%